Visual Design on Mobile Learning: การออกแบบทางทัศนะสำหรับโมบายเลิร์นนิง - Chuensombut, Suebwong (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
Mobile learning or teaching via mobile devices plays a vital role in education nowadays because it decreases the limit of learning in class. With anytime and anywhere learning, learners can access a lot of resources faster than other media via internet network by using mobile devices. Thus, not only activities, but also visual design can help learners be able to understand various contents or many lessons from mobile learning. Visual design is about texts, characters, pictures, graphics, colors including area design on the mobile devices. To design all aspects clearly, these things motivate learners to understand, learn, and do activities in each lesson efficiently and effectively.